Acceptability and Satisfaction of Contraceptive Vaginal Rings in Clinical Studies: A Systematic Review and Narrative Synthesis - Delvaux, Thérèse; Jespers, Vicky; Benova, Lenka; van de Wijgert, Janneke (Frontiers in Global Women's Health, 2021)
Introduction Acceptability of and satisfaction with contraceptive methods are paramount for uptake and continuation. In the current context of multipurpose prevention of pregnancy and sexually transmitted diseases /HIV development, it is critical to have a better understanding of acceptability of and satisfaction with the contraceptive vaginal ring (CVR), including sexual satisfaction. The objective of this study was to review the evidence about CVRs acceptability, and users’ general and sexual satisfaction. Methods We searched PubMed, CINAHL and Web of Science (until December 31th, 2020) and selected original studies documenting actual use of hormonal CVR and explicitly addressing any of the three outcomes. Main Results Of a total of 1129 records screened, 46 studies were included. Most studies (n=43, 93%) were prospective, conducted in high-income settings (n=35) and reported on NuvaRing® use (n=31). Overall, 27 (59%) studies included a comparison group, 38 (82%) used exclusively quantitative questionnaires, with qualitative only (n=4, 9%) or mixed methods (n=4, 9%) studies being less common. Ease of CVR insertion/removal/reinsertion was high in all setting and improved with time of use, with qualitative studies supporting these findings. When reported, results on continuation of use were mixed and ring-related events were associated with discontinuation. Among NuvaRing® studies, general satisfaction (being satisfied or very satisfied) was between 80 and 90% and tended to mirror continuation. Sexual satisfaction was less commonly reported and results were mixed. Overall, limited information was provided on actual CVR experiences of women (and men) and cultural norms that may affect sexuality and CVR use. Conclusion Positive aspects of acceptability of and satisfaction with CVR were reported but continuation rates and ring-related events deserve further study. More information is needed on actual experiences of women using CVRs, relationship aspects, male partner opinions, and contextual norms to better understand the acceptability of and satisfaction with CVRs.